2020
DOI: 10.1098/rspa.2019.0491
|View full text |Cite
|
Sign up to set email alerts
|

Method for controlling vibration by exploiting piecewise-linear nonlinearity in energy harvesters

Abstract: Vibration energy is becoming a significant alternative solution for energy generation. Recently, a great deal of research has been conducted on how to harvest energy from vibration sources ranging from ocean waves to human motion to microsystems. In this paper, a theoretical model of a piecewise-linear (PWL) nonlinear vibration harvester that has potential applications in variety of fields is proposed and numerically investigated. This new technique enables automatic frequency tunability in the energy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…With these values determined, the entire vibration cycle for any gap size can be constructed. For a more detailed explanation of the BAA method, refer to previous works on this topic [34,35].…”
Section: (B) System Dynamicsmentioning
confidence: 99%
See 3 more Smart Citations
“…With these values determined, the entire vibration cycle for any gap size can be constructed. For a more detailed explanation of the BAA method, refer to previous works on this topic [34,35].…”
Section: (B) System Dynamicsmentioning
confidence: 99%
“…This process is then repeated during the operation of the device. The previous computational study showed that this design performs more effectively than many other VEHs for a number of cases since it can operate efficiently for a wide variety of excitation conditions [34].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Yao et al [23] attached a nonlinear energy sink (NES) with piecewise linear stiffness to suppress the vibration of a forced primary vibration system, and the effectiveness of the NES was proven by experiments. In design of energy harvesters, Tien and D'souza [24] proposed a new vibration harvester composed of a piecewise linear oscillator and an adjustable gap, which has an optimal vibration performance over a broad frequency range and the best performance at resonance. Zhang et al [25] experimentally designed a vibration harvester with piecewise linear stiffness characteristic, which may work in a broadband and low-frequency range.…”
mentioning
confidence: 99%